PENGARUH KONSENTRASI PACLOBUTRAZOL TERHADAP PERTUMBUHAN DAN PERKEMBANGAN VARIETAS TANAMAN CABAI RAWIT (Capsicum frutescens L.) - azizah nur (Department of Agronomy Faculty of Agriculture University of Mataram and Indonesian Society of Agronomy Branch NTB, 2019)
This objective of this research is to know ot the effect of Paclobutrazol on the growth and development of Cayenne pepper (Capsicum frutescens L.). The research was conducted at the Greenhouse Faculty of Agriculture, Mataram University, starting in August to November 2018. The Factorial Completely Randomized Design (CRD), was used in this research with 2 factors. The first factor is the growth regulator p0 control (Water), p1 solution of Paclobutrazol concentration of 30 ppm, p2 solution of Paclobutrazol concentration of 30 ppm, and p3 solution of Paclobutrazol concentration of 30 ppm, second factor is varieties of chili plants, v1: varieties of Mmaruti, and v2: F1 Dewata varieties. So that, It’s gained four times so that were 32 experimental units. Data were analyzed by Analysis of variance (ANOVA) and further tested using HonestlySignificant Difference (HSD) at the 5% level. The research results indicated p0 (Water), concentrations p1 (30 ppm), p2 (60 ppm), and p3 (90 ppm) did not affect the growth and development of Cayenne pepper (Capsicum frutescens L.). The interaction between Paclobutrazol and Cayenne (Maruti and Dewata F1) varieties did not affect the growth and development of Cayenne pepper (Capsicum frutescens L.). Variety factors have an influenced on plant height at the ages of 7, 14, 21, 35, 42 days after planting, and the stem dry weight of Cayenne.